Analysis of climate variability : applications of statistical techniques : proceedings of an autumn school organized by the commission of the European Community on Elba from October 30 to November 6, 1993 - Storch, H. v. (Hans von), 1949-; Navarra, A. (Antonio), 1956-; Commission of the European Communities (New York : Springer Verlag, 1999)
40